A Study on the Surface Properties of Transition Metal Oxides - Prabhunath Misra, Muralidhara K, (International Journal of Scientific Research and Management (IJSRM), 2014)
Transition metal oxides show many interesting phenomena from high-Tc superconductivity to colossal magneto-resistance and multi-ferroicity, triggering intensive studies. However, we have barely tapped into their potential for applications. Oxides, often considered as synonymous with ceramics, bring terms such as china dishes or pottery to mind. However, oxides with transition metals that straddle the subtle boundary between covalent, ionic and metallic bonding show copious physical phenomena, ranging from highTcsuperconductivity in layered cuprates, colossal magnetoresistance (CMR) in perovskite manganites, to the coexistence of magnetism and ferroelectricity — termed multiferroicity.